Duch Is Dead Review of: Alexander Laban Hinton, Man or Monster? — The Trial of a Khmer Rouge Torturer (Durham, NC: Duke University Press, 2016). 360 pp. 22 illustrations. $26.95 (pb). ISBN: 978-0-8223-6273-9. (2017) - Bouwknegt, Thijs
No abstract available